The quark condensate in multi-flavour QCD – planar equivalence confronting lattice simulations - Adi Armoni (Physics Letters B, 2015)
Planar equivalence between the large N limits of N = 1 Super Yang-Mills (SYM) theory and a variant of QCD with fermions in the antisymmetric representation is a powerful tool to obtain analytic non-perturbative results in QCD itself. In particular, it allows the quark condensate for N = 3 QCD with quarks in the fundamental representation to be inferred from exact calculations of the gluino condensate in N = 1 SYM. In this paper, we review and refine our earlier predictions for the quark condensate in QCD with a general number nf of flavours and confront these with lattice results.